Target to treatment: A charge to develop biomarkers of response and tolerability in child and adolescent psychiatry. Issue 4 (10th January 2022) - Stancil, Stephani L.; Tumberger, John; Strawn, Jeffrey R.
Abstract: The current pediatric mental health crisis is characterized by staggering rates of depression, anxiety, and suicide. Beyond this, first‐line pharmacologic interventions for depressive and anxiety disorders in children and adolescents produce variable responses with two in five youths failing to respond. Given the heterogeneity of treatment response in pediatric depressive and anxiety disorders, pharmacodynamic biomarkers are necessary to develop precision therapeutics by identifying clear targets to guide treatment. This mini‐review summarizes candidate biomarkers and their development in pediatric mental health conditions. A framework for how these biomarkers may relate to safety, efficacy (e.g., surrogates for clinical endpoints), tolerability or target engagement (i.e., drug action) in children and adolescents is also presented. Taken together, accumulating data suggest that, in children and adolescents with myriad psychiatric disorders, pharmacodynamic biomarkers could facilitate developing drugs with well‐defined targets in specific populations, could inform treatment decisions, and hasten patients' recovery.